Prolonged-release solid dispersions of ibuprofen - Hugo Almeida, Maria Helena Amaral, Paulo Lobao (Journal of Applied Pharmaceutical Science)
Ibuprofen (IB) is one of the most important non-steroidal anti-inflammatory drugs used in the treatment of inflammatory chronic diseases. This drug presents, in the pure state, poor physical and mechanical characteristics and their use in solid dosage forms needs the addition of excipients which improve these properties. The selection of the best excipients and the suitable pharmaceutical dosage form to carry ibuprofen are very important for the industrial success of this drug. Thus, in this work, solid dispersions of ibuprofen in cethyl alcohol (SD CA), stearic acid (SD SA) and hydrogenated castor oil (SD HCO) were prepared in order to improve physical and mechanical characteristics of this drug. Physical mixtures with the same composition of solid dispersions were also prepared. Solid dispersions of ibuprofen with stearic acid and hydrogenated castor oil showed better flow characteristics than pure ibuprofen and the respective physical mixtures. Gelatin capsules filled with solid dispersions were submitted to dissolution tests in order to study the influence of the prepared systems in the release profiles of ibuprofen. Prolonged-release of ibuprofen was achieved with the solid dispersions prepared with the different types of excipients.
Keywords: Ibuprofen,Solid dispersions,Physical mixtures,Hydrogenated castor oil,Stearicacid,Cethyl alcohol.